Hyperglykämie und Frühgeborene: Ein Kapitel für sich - Heimann, K.; Karges, B.; Goecke, T. W.; Orlikowsky, T. (Zeitschrift für Geburtshilfe und Neonatologie, 2013)
Antenatally, glucose maintenance takes place via transplacental transfer from mother to fetus. In the third trimester, the amount of glucose transported increases, while glycogen and fat stores are developed. After delivery a continuous and sufficient glucose supply for vital organs and brain is essential. In term infants hormonal and metabolic adaption is well-coordinated, involving adrenal gland, pancreas and liver. However, in preterm infants, mainly during first week of life, there is a high risk of abnormalities in glucose homeostasis. Due to limited glycogen and fat stores, hypoglycaemia may occur which is avoided by continuous glucose infusion. An underestimated risk is hyperglycaemia due to a combination of relative insulin deficiency and insulin resistance, associated with increased mortality and morbidity. Management of hyperglycaemia is one of the topics in neonatology and is still being discussed controversially. This review approaches different therapeutic strategies and gives an overview about the current recommendations in the literature.
Keywords: glucose homeostasis; premature infants; hyperglycaemia